Creep of a nickel-based single-crystal superalloy during very high-temperature jumps followed by synchrotron X-ray diffraction. (1st February 2015) - le Graverend, Jean-Briac; Jacques, Alain; Cormier, Jonathan; Ferry, Olivier; Schenk, Thomas; Mendez, José
Abstract: Complex thermomechanical loadings at high temperature ( T ⩾ 950 °C) on the AM1 single-crystal superalloy were studied by X-ray diffraction under synchrotron radiation. This technique enables in situ access to the evolutions of the lattice mismatch as well as the volume fraction and the dislocation density of the γ and γ′ phases during high-temperature non-isothermal creep loadings. It is shown that the large microstructure evolutions through the growth/shrinkage of γ/γ′ interfaces due to the γ′ volume fraction changes and the associated variations in the density of dislocations at these interfaces during temperature jumps are key parameters controlling the whole behavior (distribution of internal stresses and constitutive laws) of both phases. We propose an empirical constitutive law linking the strain rate of the γ′ phase to its stress state as well as a way to determine it. During our experiments, the plastic behavior of the γ′-rafts is related to the entry of dislocations with Burgers vectors perpendicular to the tensile axis and controlled by the overcoming of a threshold stress corresponding to the internal stress components perpendicular to the tensile axis.